Elephantiasis nostras verrucosa: case report - Pereira de Godoy, Jose Maria; Pereira de Godoy, Livia Maria (International Journal of Research in Dermatology, 2023)
Lymphedema is a clinical condition in which an accumulation of macromolecules occurs in the interstitial space and an atypical evolution known as elephantiasis nostras verrucosa may occur. The objective of this study is to report on the clinical evolution and analysis of the progression of a 56-year-old patient with a diagnosis of primary bilateral stage II lymphoedema. With an atypical presentation of it, identified as elephantiasis nostra verrucosa. The patient had suffered from lymphoestatic edema since he was 10 years old, having previously received ineffective treatments until he arrived at the Clinica Godoy in Sao Jose de Rio Preto Brazil, where he underwent an intensive therapy procedure treatment model proposed by Godoy and Godoy; in which favorable results were obtained in a short period of time. Lymphedema is a chronic disease that is manageable but not curable. It is also difficult to be treated, especially if it has progressed to a late stage such as elephantiasis nostras verrucosa associated the continuous and repetitive infectious and inflammatory processes over time must have contributed to the evolution of the fibrotic pattern. Intensive treatment based on the Godoy method® is possible reduce in short period of time the volume and improve fibrosis and quality of life this patient.